The relation between serum anti-Mullerian hormone levels and follicle count in polycystic ovary syndrome - Tanrıdan Okcu, Nefise; Nazik, Hakan; Topcu Akduman, Ayşe; Uncu, Gürkan (The European Research Journal, 2018)
Objective. Polycystic ovary syndrome (PCOS) is one of the most common endocrine disorders, affecting up to 10% of reproductive-age women. Anti-Mullerian hormone (AMH) is a member of the transforming growth factor β family and has an inhibitory effect on primordial follicle recruitment in the ovary. The study aimed to investigate the importance of serum AMH levels in the different phenotypes of PCOS and find the optimal cut-off level of AMH in PCOS patients. Methods. This was a prospective clinical trial in which diagnoses of 50 PCOS patients based on Rotterdam revised criteria were compared to 50 normo-ovulatory cases. Additionally, the PCOS group was divided into 2 subgroups based on 2 or 3 Rotterdam criteria and compared to 50 normo-ovulatory cases. Results. When compared with the control group, the AMH levels of the PCOS group were significantly higher than those of the control group (6.81 ± 2.8 ng/ml vs. 3.22 ± 2.2 ng/ml, p < 0.001). In the subgroup analysis, the AMH levels of Group 1 and Group 2 were significantly higher than those of the control group (p < 0.001). The AMH cut-off value of 4.1 ng/ml was found to distinguish healthy women from PCOS patients, with 84% sensitivity and 80% specificity. Conclusions. Subgroup analyses showed higher levels of AMH in the severe PCOS group, but the difference was not statistically significant. More studies are suggested for researching the different PCOS subgroups to detect optimal AMH thresholds.